Determining Good Practice For BCG Therapy Of Urinary Tract Cancer By Using A Knowledge Model - Iwai, Sachiko; Ishino, Fukuya (Journal of Knowledge Management Practice, 2010)
This study aimed to predict the recurrence of carcinoma following Bacillus Calmette-Guérin (BCG) therapy, an effective treatment for urothelial carcinoma. In everyday practice, cytodiagnosis of cells of the whole urinary tract is performed because it is not possible to identify and isolate the bladder or the cancerous cells of the upper urinary tract and the affected sites. We performed statistical analysis on the entire urinary tract using urine cytology specimens of patients with urinary tract cancer who had undergone BCG therapy. Subsequently, we developed a formula for predicting the recurrence of urothelial carcinoma by statistical analysis of 17 parameters in each patient. Validation based on this prediction formula yielded a hitting ratio of 80.4%. The number of BCG injections was minimized to avoid excessive side effects, and we determined the relationship between cancer recurrence, treatment and side effects. These results provide good practice guidelines for the treatment of individual patients.
Keywords: knowledge management; Good practice; Knowledge model; BCG therapy; Recurrence; Urinary tract cancer